The impacts of mural arts on tourism among millennial generation / Joeaiza Juhari ... [et al.] - Juhari, Joeaiza; Mamat, Siti Nurulhuda; Nik Mohd Masdek, Nik Rozila; Ahmad, Khaizie Sazimah (2022)
Tourism industry is known as one of the largest industries that contributed to the economic growth in Malaysia. In 2019, around 86.1 billion Ringgit Malaysia was contributed from the tourism sector (Tourism Malaysia, 2019). The number of tourists was constantly increasing over the nine consecutive years since 2011. There are many contributing factors that lead to the increasing number of tourists in Malaysia. The uniqueness and diversification of culture, arts and heritage were one of contributable factors. In Melaka, mural arts can easily be found in the old buildings, schools, universities and many other structures. It becomes one of the attractive spots for the tourists to take photographs whilst travelling around the town. This paper aims to discover the impacts of mural arts on the tourism industry based on the previous works of literature and findings on the local tourist spots in Malaysia. In addition, this paper also examines how millennial generation appreciated and perceived mural arts in the tourism industry.